Panfletagem digital – espaço público, comunicação institucional e internet - Oliveira, José Aparecido de (Horizonte, 2007)
This article is part of a research work on the discussion spaces created by the Internet for the clergy and lay members of the Methodist Church, in the months preceding the 18th General Council, carried out in 2006, and resulting in the institution’s withdrawing from the ecumenical organisms where it worked and which it help founding. The research aimed at evaluating the possibilities and limitations of the Internet as an emerging public space opened to institutions. The analysis was based on the literature concerning the history of communication media; political communication, public space and political marketing. The historical background focused on the phenomena of Protestant Reform and the Methodist Movement in 18th–century England. Results indicate that the new technologies pose challenges to institutions, such as the paradox democratization-fragmentation of authority.